THE CHALLENGE OF SECULAR HUMANISM TO CHRISTIANITY - John C. Robertson, Jr. (Journal of Dharma, 1995)
There is clearly something about the modern phase of world history,in the West at least, that is causing the sense of the presence of God to grow very dim for an increasingly large number of people.Naturally, Asia has its own history, resources, opportunities, and problems,but in so far as Western history is entering into the experience of the rest of the world, one may well anticipate that the spiritual crisis of the West will be replicated globally.